2017
DOI: 10.21608/zumj.2017.4447
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnetic Resonance Musculoskeletal Imaging in Evaluation of Sports Injuries of the Knee Joint

Abstract: Aim: to evaluate the role of magnetic resonance imaging in the assessment of sport injuries of the knee joint as an integral part of the musculoskeletal system. Methods: This study was done as a combined study between the Radiology Department of Zagazig University and the Radiology Department of University of California San Diego. It was conducted on 50 patients who were referred to the Radiology Department of the University of California San Diego. The patients were examined after sustaining different sports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thiga et al 21 found that the sensitivity and specificity of MRI for anterior cruciate ligament rupture (whether complete or partial) was 83.3% and 90.9% respectively. Similarly, Similarly, Amr et al 22 found that in comparison with knee arthroscopy, magnetic resonance imaging revealed an overall of 93.9% sensitivity and 66.6% specificity. Chiranjib et al 23 also found that the sensitivity of MRI for diagnosis of ACL was 87.5%, specificity was 66.67%, positive predictive value -87.5%, negative predictive value -66.6% and accuracy of 81.82%.…”
Section: Discussionmentioning
confidence: 82%
“…Thiga et al 21 found that the sensitivity and specificity of MRI for anterior cruciate ligament rupture (whether complete or partial) was 83.3% and 90.9% respectively. Similarly, Similarly, Amr et al 22 found that in comparison with knee arthroscopy, magnetic resonance imaging revealed an overall of 93.9% sensitivity and 66.6% specificity. Chiranjib et al 23 also found that the sensitivity of MRI for diagnosis of ACL was 87.5%, specificity was 66.67%, positive predictive value -87.5%, negative predictive value -66.6% and accuracy of 81.82%.…”
Section: Discussionmentioning
confidence: 82%
“…The anatomical structure of the knee joint is complex, and it bears the weight and greater stress of the body. Its stability is poor, so the knee joint is easy to be injured [8]. The knee joint injury is shown in Figure 1.…”
Section: Treatment Of Knee Joint Injurymentioning
confidence: 99%
“…Linklater et al studied imaging of acute capsular ligament sports injuries of the ankle and foot and found that diagnostic imaging was helpful in assessing persistent symptoms in subacute or chronic settings [2]. Khalil et al explored the role of magnetic resonance musculoskeletal imaging in the assessment of knee sports injuries [3]. Yasuhiro explored gender-related diferences in lower extremity alignment, range of motion, and history of lower extremity sports injuries among Japanese college athletes.…”
Section: Introductionmentioning
confidence: 99%